Back Cover, Volume 39, Issue 12. Issue 12 (17th November 2018) - Schubert, Jeffrey; Tariq, Muhammad; Geddes, Gabrielle; Kindel, Steven; Miller, Erin M.; Ware, Stephanie M.
Abstract : On the Back Cover : This cover image is based on the Research Article Novel pathogenic variants in filamin C identified in pediatric restrictive cardiomyopathy by Jeffrey Schubert et al., Pages 2083–2096. DOI:10.1002/humu.23661 .